Pengembangan Modul Ajar Berbasis Problem-Based Learning Untuk Meningkatkan Keterampilan Komunikasi Siswa Kelas IV SD - Vinsensia Kewa Lolong; Rusmawan Rusmawan (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
This study, entitled The Development of a Problem-Based Learning-Based Teaching Module on the Application of Pancasila Principles to Improve the Communication Skills of Fourth-Grade Elementary School Students, was motivated by the low communication skills of elementary school students and the unavailability of teaching modules specifically designed to develop these skills through meaningful learning. This study aimed to describe the process of developing a Problem-Based Learning (PBL)-based teaching module to improve the communication skills of fourth-grade elementary school students.This research employed a Research and Development (RD) method using the ADDIE development model, which consists of the stages of analyze, design, develop, implement, and evaluate. The research subjects were 20 fourth-grade students of SD Kanisius Kalasan. Data were collected through observation, interviews, questionnaires, and document analysis. The developed teaching module was validated by four experts, consisting of two subject-matter experts and two instructional experts. The validation results showed that the teaching module obtained an average score of 3.56, categorized as very valid in terms of module readability, structural feasibility, integration of the PBL model, and integration of communication skills. The findings indicate that the developed PBL-based teaching module is feasible to be used as instructional material to support the improvement of communication skills of fourth-grade elementary school students.ABSTRAKPenelitian berjudul Pengembangan Modul Ajar Penerapan Sila-Sila Pancasila berbasis Problem Based Learning untuk Meningkatkan Keterampilan Komunikasi Siswa Kelas IV SD yang dilatarbelakangi oleh rendahnya keterampilan komunikasi siswa sekolah dasar serta belum tersedianya modul ajar yang secara khusus dirancang untuk mengembangkan keterampilan tersebut melalui pembelajaran yang bermakna. Penelitian ini bertujuan untuk mendeskripsikan proses pengembangan modul ajar PBL untuk meningkatkan keterampilan komunikasi siswa kelas IV sekolah dasar. Penelitian ini menggunakan metode Research and Development (RD) dengan model pengembangan ADDIE yang meliputi tahap analyze, design, develop, implement, dan evaluate. Subjek penelitian adalah 20 siswa kelas IV SD Kanisius Kalasan. Teknik pengumpulan data dilakukan melalui observasi, wawancara, kuesioner, dan studi dokumen. Produk modul ajar yang dikembangkan divalidasi oleh empat ahli yang terdiri atas dua ahli materi dan dua ahli pembelajaran. Hasil validasi menunjukkan bahwa modul ajar memperoleh skor rerata sebesar 3,56 dengan kategori sangat valid ditinjau dari aspek keterbacaan modul, kelayakan struktur modul, integrasi model PBL, dan integrasi keterampilan komunikasi. Hasil penelitian ini menunjukkan bahwa modul ajar berbasis PBL yang dikembangkan layak digunakan sebagai bahan ajar untuk mendukung peningkatan keterampilan komunikasi siswa kelas IV sekolah dasar.